Goal Orientations and Activation of Approach Versus Avoidance Motivation While Awaiting an Achievement Situation in the Laboratory - Wimmer, Sigrid; Lackner, Helmut K.; Papousek, Ilona; Paechter, Manuela (Frontiers in Psychology, 2018)
While some students try to give their best in an achievement situation, others show disengagement and just want to get the situation over and done with. The present study investigates the role of students’ tendencies for approach or avoidance motivation while anticipating tasks and the corresponding activation of the approach/avoidance motivational system as indicated by transient changes of EEG alpha asymmetry. Overall, 62 students (50 female; age: M = 23.8, SD = 3.5) completed a goal orientation questionnaire (learning goals, performance-approach, performance-avoidance, work avoidance). They joined a laboratory experiment where EEG was recorded during resting condition as well as when students were anticipating tasks. Standard multiple regression analysis showed that higher values on performance-avoidance were related to a higher activation of the approach system whereas higher values on work avoidance were related to a higher activation of the avoidance system. Results question present assumptions about avoidance related goal orientations.